Evaluation of Major Land Uses in Tertiary Institution: A Case Study of Obafemi Awolowo University Ile Ife, Nigeria - Olusola Oladapo Makinde; Muhammad Ridwan; M. Yoserizal Saragih (Budapest International Research and Critics University, 2021)
Land uses involve important economic and environmental implications for policy issues. To monitor the trend in land use in tertiary institution, statistics on land use overtime must be developed. The study investigated the various uses of land in Obafemi Awolowo University (OAU); determine their size base on an area of land covered, and determine the major land uses in OAU to inform planners on the basic tool for institutional physical development and insight for enhancing planning. The Google earth pro and OAU base map were subsequently used to enhance visual interpretation and aid the identification and mapping of the various land use in the study area. Findings from the study show that the total landed area is 5,609 hectares. The undeveloped area constitutes more than half of the total landed area with 3382 hectares (60 %). A total of 1,216 hectares of land was set aside for agriculture purposes and research, the major land uses is residential with 456.74 hectares (45.18%); institutional uses had 257.02 hectares (25.42%); other uses had 115.97 hectares (11.47%); water bodies had 83.5 hectares (8.26%); transportation had 56.33 hectares (5.57%); commercial had 38.36 hectares (3.79%); and Recreation had 3.08 hectares (0.31 %), the least proportion of land use. The study concluded that land use should be monitored, regulated, and controlled by the various relevant planning and monitoring agencies of the university.